Campus Information Sharing and Responses to Sexual Misconduct Violations: An Exploratory Study - Shields, Ryan T. (Journal of interpersonal violence, 2022)
Recent years have seen growing public interest in how college and university administrators respond to sexual misconduct. Despite policy changes in this area, minimal research exists on how institutions of higher education (IHEs) are sharing and processing information about students found responsible for sexual misconduct. Aiming to establish some of the key questions and parameters in this line of research, this practitioner?researcher collaboration offers a first look at how IHEs share information about students who have been found responsible both within their campus and between campuses, as well as how IHEs respond when that information is shared (e.g., admitting a student applicant who has been previously sanctioned for a sexual misconduct violation). Practitioners designed and disseminated a questionnaire to campus administrators, including Title IX coordinators and student conduct administrators, via higher education association listservs. Exploratory results from 176 participants showed that 80% reported having some form of policy regarding sharing information within their institution, while approximately half have policies regarding sharing information to other IHEs regarding students found responsible of sexual misconduct. Nearly one-third of participants reported that their IHEs are engaging in campus information sharing through the use of transcript notation. In terms of IHEs receiving information about student applicants having been previously sanctioned for a sexual misconduct violation, approximately one-fourth of participants indicated their IHE has chosen not to accept a student for this reason within the past 5 years, and a quarter of IHEs have accepted such students. For those IHEs that have accepted a student previously found responsible, the majority of IHEs are not following the outcomes of these students, indicating an unknown in terms of whether information sharing policies were effective. As a result, preliminary findings suggest that more evaluation research is needed before any further policies are mandated.